1999
DOI: 10.1034/j.1600-051x.1999.260707.x
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the inflammatory response in young and old human subjects during the course of experimental gingivitis

Abstract: The aim of the present experiment was to study changes in (i) the composition of the inflammatory cell infiltrates and (ii) levels of alpha 2-macroglobulin, lactoferrin and IgG subclasses in gingival crevicular fluid in young and old individuals during 3 weeks of plaque formation. To establish healthy gingival conditions, all subjects received professional tooth cleaning during a 4 week pre-experimental period. The experimental sites included the mesio-palatal, palatal, and disto-palatal surfaces of all teeth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
47
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 31 publications
10
47
0
3
Order By: Relevance
“…This seems contradictory to what is generally accepted; dental plaque leads to gingival inflammation when it is present on the tooth surface for a longer period [26]. One determining factor in the development of gingival inflammation is patient susceptibility towards the presence of dental plaque [27, 28]. Furthermore, the assumption that only old plaque causes gingival bleeding does not take the microbiological characteristics of the plaque biofilm into account.…”
Section: Discussionmentioning
confidence: 97%
“…This seems contradictory to what is generally accepted; dental plaque leads to gingival inflammation when it is present on the tooth surface for a longer period [26]. One determining factor in the development of gingival inflammation is patient susceptibility towards the presence of dental plaque [27, 28]. Furthermore, the assumption that only old plaque causes gingival bleeding does not take the microbiological characteristics of the plaque biofilm into account.…”
Section: Discussionmentioning
confidence: 97%
“…Die Anhaftung von Plaque auf den palatinalen Zahnoberflächen untersuchten Fransson et al [12,13] bei gesunden Probanden ohne kieferorthopädische Behandlung. Trotz einer quantitativ ähnlichen Plaqueakkumulation entwickelten die älteren Probanden (65-80 Jahre) mehr Gingivitis als die jüngeren (20-25 Jahre), was auf eine schwächere Abwehrreaktion der älteren Probanden schließen lässt.…”
Section: Methodsunclassified
“…Specific plaque accumulation in the palatal regions was examined by Fransson et al [12,13] in individuals not undergoing orthodontic treatment. They found that older individuals (65-80 years) formed similar amounts of plaque to younger individuals (20-25 years), but tended to develop more gingivitis than the younger subjects, suggesting that this area may be more vulnerable in the elderly.…”
Section: Introductionmentioning
confidence: 99%
“…A study comparing experimental gingivitis in young vs. old individuals by Fransson et al [2,3] did confirm that older individuals experience more severe inflammation in response to experimental gingivitis. Nevertheless, several studies evaluating whether age is a risk factor for increased loss of periodontal support, have shown that aging either has no effect at all or, if so, the effect is minor and clinically insignificant [4-8] and that smoking has much more influence than age [9].…”
Section: Introductionmentioning
confidence: 99%